A companion to the anthropology of American Indians - Biolsi, Thomas, 1952- (Blackwell companions to anthropology ;, 2004)
"A Companion to the Anthropology of American Indians contains 27 original contributions by leading scholars who work actively as researchers in American Indian communities, or on the topic of American Indians. The book summarizes the state of anthropological knowledge of Indian peoples, as well as the history that got us to this point."--Jacket